Chemical exchange–sensitive spin‐lock (CESL) MRI of glucose and analogs in brain tumors. Issue 2 (23rd March 2018) - Jin, Tao; Iordanova, Bistra; Hitchens, T. Kevin; Modo, Michel; Wang, Ping; Mehrens, Hunter; Kim, Seong‐Gi
Abstract : Purpose: Glucose uptake and metabolism can be measured by chemical exchange–sensitive spin‐lock (CESL) MRI with an administration of glucose or its analogs. This study investigates the sensitivity, the spatiotemporal characteristics, and the signal source of glucoCESL with a 9L rat brain tumor model. Methods: Dynamic CESL MRI with intravenous injection of D‐glucose, 2‐deoxy‐D‐glucose (2DG), and L‐glucose were measured and compared with gadolinium‐based dynamic contrast‐enhanced (DCE) MRI. Results: The CESL signals with an injection of glucose or analogs have faster and larger changes in tumors than normal brain tissue. In tumors, the CESL signal with 2DG injection has larger and slower peak response than that with D‐glucose due to the accumulation of 2DG and 2DG‐6‐phosphate in the intracellular compartment, whereas L‐glucose, which cannot be transported intracellularly by glucose transporters, only induces a small change. The initial glucoCESL maps (< 4 minutes) are qualitatively similar to DCE maps, whereas later maps (> 4 minutes) show more widespread responses. The rise times of D‐glucose‐CESL and 2DG‐CESL signals in the tumor are slower than that of DCE. Our data suggest that the initial CESL contrast primarily reflects a passive increase of glucose content in the extracellular space of tumors due to a higher vascular permeability, whereas the later period may have a significant contribution from the uptake/metabolism of glucose in the intracellular compartment. Conclusions: Our results demonstrate that glucoCESL MRI has both extracellular and intracellular contributions, and can be a useful tool for measurements of both vascular permeability and glucose uptake in tumors.